2009
DOI: 10.2478/v10034-009-0007-7
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Causes of Congenital Anomalies in the Pleven Region, Bulgaria

Abstract: Trends and Causes of Congenital Anomalies in the Pleven Region, BulgariaWe describe the secular trend, pattern and causes of congenital anomalies (CAs) in the Pleven region, Bulgaria. The source of the data was the regional population-based registry of CAs using criteria according to EUROCAT recommendations. During the period 1988-2006, 47,622 births were surveyed. A total of 1,225 cases of CAs were ascertained, giving a total prevalence of 25.72 [95% confidence interval (95% CI) 24.3 to 27.15 per 1,000 births… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…However, the numbers for the malformations of the specific body system were small for any statistical power in the analysis. Similar observations have been made in other long-term studies from the developed countries [ 7 , 13 , 22 , 30 , 31 , 35 ]. There were no long-term population based studies from the English speaking Caribbean region available for comparison.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the numbers for the malformations of the specific body system were small for any statistical power in the analysis. Similar observations have been made in other long-term studies from the developed countries [ 7 , 13 , 22 , 30 , 31 , 35 ]. There were no long-term population based studies from the English speaking Caribbean region available for comparison.…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrates a significant increase in the prevalence of MCMs when the prevalence rate for the period 1993 to 2002 was compared with those from the period 2003-2012. Long-term studies from other countries have reported varying secular trends in the prevalence of CMs [ 7 , 13 , 22 , 30 , 31 , 35 ]. Studies from UK and the USA have reported an overall decreasing trend and have attributed the decline to increasing prenatal diagnosis and termination of pregnancy in addition to the factors mentioned above [ 22 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current review, the pooled proportion of chromosomal disorders in Africa was 8.94 (CI: 7.02, 10.86: I 2 : 98.8%; p < 0.001). The result of this meta analyses is comparable with a large-scale study conducted in Bulgaria: in which the proportion of chromosomal disorders was 8.2% among births with congenital anomalies [ 97 ]. The current result is higher compared to the study conducted in industrialized nations, in which only 6% of chromosomal disorders accounted for among births with congenital anomalies [ 98 ].…”
Section: Discussionsupporting
confidence: 82%
“…8,9 The study of missing frequency of congenital cardiac anomalies will be important in planning for prevention strategies, medical care, and surgical treatment of newborn babies. 10,3 Infants with congenital cardiac diseases may not even be diagnosed until a paediatric cardiologist visits them for some other medical reasons. 11,12 The aim of this study was to estimate the missing frequency of congenital cardiac anomalies at the time of delivery or after birth.…”
mentioning
confidence: 99%
“…Early diagnosis and screening of congenital cardiac anomalies is vital because the lack of proper diagnosis of congenital cardiac malformation will result in a high risk of mortality in children and decrease life expectancy of newborn infants 8 , 9 . The study of missing frequency of congenital cardiac anomalies will be important in planning for prevention strategies, medical care, and surgical treatment of newborn babies 10 , 3 . Infants with congenital cardiac diseases may not even be diagnosed until a paediatric cardiologist visits them for some other medical reasons 11 , 12 .…”
mentioning
confidence: 99%